DISCOURSE AND THIRD SPACE IN FRANK MCCOURT’S NOVEL "TEACHER MAN" AND TOM SCHULMAN’S PLAY "DEAD POETS SOCIETY"; A REFLECTIVE PRACTICE FOR TEACHERS - Eka Sugeng Ariadi (EduLite: Journal of English Education, Literature and Culture, 2017)
Pahl and Rowsell (2005) elucidate that Discourse is ways of dressing, speaking and acting which delineates person’s identities in literacy practices, while a third space is as a meeting spaces between home space and school space, blend and mix space, in which lets teachers think how their students’ meaning-making are happened between school and home. This paper investigates how these theories are fruitfully presented in the character of Mr. McCourt Teacher Man and Mr. Keating Dead Poets Society. Subsequently, it is interconnected with educational theory A taxonomy for Learning, teaching, and assessing: A revision of Bloom’s taxonomy of educational objectives, as recommended by Anderson and Krathwohl (2001). The result shows that the Metacognitive Knowledge domain prominently becomes the intersection as it is emphasizing on the student’s awareness of one’s own cognition and cognitive processes, particularly contextualizing students’ knowledge and general knowledge. Mr. McCourt and Mr. Keating have succeeded in shifting frighten and strict classroom situation generated by most teachers become so challenging and much interesting by utilizing multimodal styles and skills, and piloting third space activity. Henceforth, the writer recommends teachers to maximize their own potentials characters to accommodate their students’ preferences or styles in learning the subjects. In addition, designing teaching and learning process in-between home and school is necessary to be done, in order to contextualizing and perceiving real life experiences.